The association of thiol/disulphide homeostasis and lipid accumulation index with cardiovascular risk factors in overweight adolescents with polycystic ovary syndrome. (25th November 2015) - Ozler, Sibel; Oztas, Efser; Tokmak, Aytekin; Ergin, Merve; Isci, Esra; Eren, Funda; Pehlivan, Selcen; Neselioglu, Salim; Yılmaz, Nafiye
Summary: Objective: To assess thiol/disulphide homeostasis and lipid accumulation product index, and to determine whether they are associated with increased cardiovascular disease (CVD) risk or not in overweight adolescents with polycystic ovary syndrome (PCOS). Design: Case–control study. Setting: Education and Research Hospital. Patients: Group 1: 43 overweight+PCOS, Group 2: 45 normal weight+PCOS, Group 3: 27 overweight adolescents and Group 4: 96 age‐matched, normal weight healthy controls. Interventions: Serum lipid profiles, hormonal parameters and thiol/disulphide homeostasis were measured. Lipid accumulation index (LAP index) and homeostasis model assessment (HOMA‐IR) were calculated. Main outcome measures: The relation between thiol/disulphide homeostasis and LAP index, and increased CVD risk were evaluated in overweight adolescents with PCOS. Results: Native and total thiol levels were significantly lower in overweight+PCOS adolescents when compared with both normal weight PCOS and control adolescents ( P = 0·002). LAP index values were significantly higher in Group 1 when compared separately with the rest of the three groups ( P < 0·001). Multivariable logistic regression analysis revealed serum total thiol levels of lower than 405·45 μmol/l were independently associated with increased risk of CVD in overweight PCOS adolescents (OR: 1·019, 95% CI: 1·001–1·036). In addition, a LAP index greater than 21·54 was also associated with increased CVD risk in overweight PCOS adolescents (OR: 1·270, 95% CI: 1·174–1·374). Conclusion: In conclusion, we suggest that increased LAP index and decreased total thiol levels may contribute to the increased CVD risk in overweight adolescents with PCOS.